Early Childhood Family Learning Environment's Influence on Adolescent Learning Achievement in Taiwan. Issue 2 (May 2015) - Lin, Chunn-Ying; Chen, Cheng-Hung
THIS STUDY USED FOUR waves of the Taiwan Education Panel Survey (TEPS) for seventh to twelfth grade students to construct a latent growth model (LGM) and carry out a longitudinal analysis, in order to explore the influence of the early childhood family learning environment on later adolescent learning achievement, performance and change. The results showed that adolescents with better performance in early learning had greater growth in later learning achievements. In addition, when preschool children had a good family learning environment, it benefited their cognitive skill development before they entered elementary school, and enhanced their reading interest as well as self-education expectations. This consequence further improved adolescent learning achievements, and these advantaged children had significantly higher learning growth levels later than children without such advantages.